Analisa Perbandingan Metode Certainty Factor dan Teorema Bayes Untuk Mendiagnosa Penyakit Pneumonia Pada Anak - Dewi Yurika; Nelly Astuti Hasibuan; Edizal Hatmi (STMIK Budi Darma, 2022)
Pneumonia is a disease that causes death in children because the body's defense system is relatively low. At this time people do not really care about pneumonia because this pneumonia has symptoms that are almost the same as coughing. This happens because of the weak knowledge of parents about pneumonia. Fast and precise information and prevention from a health expert are needed by parents about the symptoms of pneumonia and how to treat it early. One alternative that the author can do for the problems that have been described, the authors make a comparison between the certainty factor method and the Bayes theorem to find the certainty value of the symptoms suffered by the patient, which will later be analyzed for the accuracy of each method. Where this study provides solutions and prevention methods so that parents can quickly find out the symptoms suffered by children so that they are not diagnosed with pneumonia. Based on the final results of the research conducted by the author of the comparison method by applying the exponential comparison method, which resulted in the certainty factor method being the most appropriate method and the highest level of accuracy for diagnosing pneumonia in children, the final result of the comparison was 14 with a diagnosis result of 99.03%. , while the Bayes theorem method the final result of the comparison is 3 with a diagnostic result of 72.38%.